Nanoparticles for Tendon Healing and Regeneration: Literature Review - Parchi, Paolo D.; Vittorio, Orazio; Andreani, Lorenzo; Battistini, Pietro; Piolanti, Nicola; Marchetti, Stefano; Poggetti, Andrea; Lisanti, Michele (Frontiers in Aging Neuroscience, 2016)
Tendon injuries are commonly met in the emergency department. Unfortunately, tendon tissue has limited regeneration potential and usually the consequent formation of scar tissue causes inferior mechanical properties Nanoparticles could be used in different way to improve tendon healing and regeneration, ranging from scaffolds manufacturing (increasing the strength and endurance or anti-adhesions, anti-microbial and anti-inflammatory properties) to gene therapy. This paper aims to summarize the most relevant studies showing the potential application of nanoparticles for tendon tissue regeneration